“My iPhone Has a Virus Called U2, How Do I Uninstall It?”: Controversies Surrounding the Digital Release of U2’s Songs of Innocence - Pietrzykowski, Szymon (Media - Culture - Social Communication, 2019)
Controversies surrounding the digital release of U2’s 13th studio record Songs of Innocence, reported extensively in this article, also served as an excuse to (i.e.) disclose the phenomenon of the Irish group or conduct more general reflections concerning the condition of modern-day music industry and attitudes towards pop culture, which are completely different among the so-called Millennials and Baby Boomers, U2 followers and supporters of other bands. However, thanks to a contract between U2 and Apple, this album reached a record number of 500 million people, but the form of its release (it was automatically added to iTunes users’ personal libraries) caused critical backlash and even hatred.